Combating antibiotic resistance: Current strategies for the discovery of novel antibacterial materials based on macrocycle supramolecular chemistry. (August 2021) - Gao, Lingyan; Wang, Haojie; Zheng, Bo; Huang, Feihe
Abstract: In the fight of bacteria with human, bacteria have regained the upper hand by development of antibiotic resistance. The emergence of resistance has outpaced the development of new antibiotics, and investment in research and development of new antibiotics is diminishing, which has caused the world entering into a post-antibiotic era for that minor injuries and common infections can kill human beings in the future. Supramolecular macrocycles, due to their unique structures, facile and versatile functionality, abundant host–guest complexation abilities, and dynamic and modular properties, have been widely explored to fabricate versatile functional materials. In particular, they have been demonstrated as useful platforms for the design of elaborate structures for antibacterial use. In this review, we will briefly present basic concepts, novel strategies, and unique antibacterial activities of different antibacterial materials based on different supramolecular macrocycles, including pillararenes, cucurbiturils, cyclodextrins, calixarenes, crown ethers, and other macrocycles, which may open an alternative way to complement traditional drugs, facilitate the development of modern medicine, and overcome the antibiotic-resistance crisis. Graphical abstract: In this review, we will briefly present basic concepts, novel strategies, and unique antibacterial activities of different antibacterial materials based on different supramolecular macrocycles, including pillararenes, cucurbiturils, cyclodextrins, calixarenes, crown ethers, and other macrocycles, which may open an alternative way to complement traditional drugs, facilitate the development of modern medicine, and overcome the antibiotic-resistance crisis. Image, graphical abstract